2017
DOI: 10.2214/ajr.16.17133
|View full text |Cite
|
Sign up to set email alerts
|

Renal Masses Detected on FDG PET/CT in Patients With Lymphoma: Imaging Features Differentiating Primary Renal Cell Carcinomas From Renal Lymphomatous Involvement

Abstract: OBJECTIVE The purpose of this study is to analyze the 18F-FDG PET/CT features of solid renal masses detected in patients with lymphoma and to evaluate the ability of PET/CT to differentiate renal cell carcinoma (RCC) from renal lymphomatous involvement. MATERIALS AND METHODS Thirty-six patients with solid renal masses on PET/CT performed for staging or follow-up of lymphoma were evaluated retrospectively. The features recorded for each renal mass included the following standardized uptake values (SUVs) on PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(62 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…11 Texture analysis of computed tomography (CT) and magnetic resonance imaging (MRI) showed promising discriminative ability in various lesions, including breast lesions, lung lesions, and so on. [12][13][14] Texture analysis on 18 F-FDG positron emission tomography (PET)/CT images also showed great diagnostic utility among lung lesions, 15 renal lesions 16 and bone and soft-tissue lesions. 11 While the possibility using radiomic features to differentiate between carcinoma and lymphoma in the breast has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…11 Texture analysis of computed tomography (CT) and magnetic resonance imaging (MRI) showed promising discriminative ability in various lesions, including breast lesions, lung lesions, and so on. [12][13][14] Texture analysis on 18 F-FDG positron emission tomography (PET)/CT images also showed great diagnostic utility among lung lesions, 15 renal lesions 16 and bone and soft-tissue lesions. 11 While the possibility using radiomic features to differentiate between carcinoma and lymphoma in the breast has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%
“…PET/CT can reveal the metabolic characters of organs, and as tumor cells have enhanced glycolysis, they have higher 18F-FDG uptake compared with normal tissue. Previous studies have indicated that the SUV metrics of lymphoma was higher than that of carcinoma in PET/CT images when differentiating renal carcinoma and lymphoma with renal involvement (14, 15). However, a study claimed that the SUV max was not conclusive when distinguishing between primary nasopharyngeal lymphoma and nasopharyngeal carcinoma (16).…”
Section: Discussionmentioning
confidence: 99%
“…21,22 However, PET/CT may be useful in distinguishing between lymphoma and RCC since the former is intensely FDG-avid while the latter may not show as much FDG uptake. 23 Traditionally, PRL has been associated with a poor prognosis. 16,[24][25][26] However, early diagnosis and proper management results in a favorable outcome.…”
Section: Discussionmentioning
confidence: 99%